التوصيف المظهري لبعض الطرز البرية لجنس اللاوندLavandula spp.المنتشرة في محافظة اللاذقية و مقارنتها بالنوع المدخل L.officinalisChaix. - نصّور, مازن; محفوض, حافظ; رضوان, ثروت (Latakia University Journal -Biological Sciences Series, 2014)
هدف هذا البحث إلى إجراء التوصيف المظهري و تحديد درجة التباين بين الطرز التابعة لجنس Lavandulaspp المنتشرة برياً في محافظة اللاذقية و مقارنتها بإحدى طرز النوع المدخلL.officinalisChaix.بهدف إنشاء نواة لبنك وراثي, و الاستفادة من الطرز ذات الصفات النوعية الجيدة بغية تحسينها مستقبلاًو العمل على تشجيع زراعتها بدلاً من استيرادها. تم دراسة 28 صفة مظهرية إضافةً لمحتوى الزيت العطري لـ 45طرازاً برياً تابعاً للجنس Lavandulaspp.في مواقع مختلفة في شمال محافظة اللاذقية. أكدت النتائج على إمكانية التفريق بين الطرز المحلية المدروسة ونباتات الطراز L.officinalisوذلك بالاعتماد على المواصفات المظهرية خاصة المتعلق منها بالنورات والبذور والثمار, والتي أعطت بحسب التحليل العنقودي أعلى نسبة اختلاف بين الطرزالمحليةو L.officinalis(98 و 65% على التوالي) في حين بلغت نسبة التشابه بين هذه الطرز في الصفات الخضرية المدروسة (60%). إضافة لما سبق فقد سجلت فروق معنويةفي نسبة الزيت العطري بين الطرز المدروسة من جهة و النوع المدخل This research aimed at conducting a morphological characterization, and determining the degree of variation between some Lavandula spp genotypes distributed in Lattakia and then comparing them with L. Officinalis. This is in order to create a gene bank, and to take advantage of high quality characteristic types to improve them in the future and to encourage their cultivation instead of importing them. 28 Phenotypic characteristics were studied for 45 types scattered at various sites north Lattakia, in addition to examining the content of essential oil and comparing it with L. officinalis Chaix.. The results showed the possibility of comparing the studied types depending on the phenotypic characteristics especially those related to spick, seeds and fruits. According to a cluster analysis, this showed the highest ratio difference between the studied plants (98% and 65% respectively), while the percentage of similarity between these types in the vegetative traits studied was 60%. Moreover, significant differences in the ratio of essential oil between the studied types and the introduced type were recorded, where the ratio of the introduced type was (2.02%), and (1.4%) in the types grown in Mishqita area